ANALISIS PERBANDINGAN KONFIGURASI PREDIKSI INTRA DAN INTER PADA PENGKODEAN H.265 - Maulida Yasmin; Arief Suryadi Satyawan; Ichwan Nul Ichsan (MULTITEK INDONESIA, 2025)
The increasing demand for high-quality video delivery and storage has driven the development of more efficient video coding. H.265 is one of the latest video coding standards that provides better compression than its predecessor, H.264. This study analyzes the impact of intra and inter prediction configurations on video compression quality and efficiency in the context of H.265 encoding. The analysis is performed using Rate-Distortion (R-D) curves for several prediction configurations on each video sequence. The experiment compares intra, lowdelay, lowdelay-P, and randomaccess configurations on several video sequences. The results show that the intra configuration achieves the highest PSNR but also the highest bitrate. On the other hand, the randomaccess configuration achieves a good balance between bitrate and PSNR, obtaining a lower bitrate with better PSNR compared to lowdelay and lowdelay-P for all sequences.